Non-catalytic green solvent lignin isolation process from wheat straw and the structural analysis. (September 2019) - Ramezani, N.; Sain, M.
Abstract: In this study, the optimal experimental conditions for extraction of organosolv lignin from wheat straw were determined. Initially, the wheat straw chemical compositions were investigated. The wheat straw held 24.6 lignin and 60% cellulose and hemicellulose on a dry weight base. The lignin extractions from wheat straw were carried out by applying 60% aqueous ethanol in a 600-mL reactor at different times (60-90-120-150 min), temperatures (100-150-200-250 °C) and pressures (300-350- 400–450 psi). The extraction was done without the use of any catalysts and all the green solvents were recovered and reused. The highest yield of lignin (90%) was obtained under optimal conditions (120 min, 200 °C, and 400 psi). The extracted lignin also contained the low amount of carbohydrate impurities and ash (2.2%). The results from Size exclusion chromatography and MALDI-TOF suggested that the number of average molecular weight and the molecular weight of extracted lignin are 7870 and 9046 Da. Extracted lignin had Coniferyl, sinapyl and coumaryl alcohols in its structure. The results from ANOVA showed that lignin extraction was mostly influenced by time, and the temperature had the least effect on it. Ultimately, to confirm the sustainability of the process, the extraction was conducted in an 18.75 L reactor. Graphical abstract: Image 1 Highlights: The highest amount of lignin from wheat straw was isolated in the absence of the catalyst by the green solvent. The considerate design was developed to lead the lignin isolation system. To extract the lignin on a large scale by using a novel method, a pilot system was implemented. Structural analysis of the lignin was conducted to identify the molecular weight and lignin subunits.